The Impact of Service-Learning (SULAM) On Civic Attitudes and Skills of Uthm Students - Nurul Izzati Asiyah Adam; Maziana Mohamed (Online Journal for TVET Practitioners, 2024)
Service learning (SULAM) is an educational approach that combines academic learning with meaningful community service. This study aims to identify the effect of the service-learning program (SULAM) on the attitudes and civic skills of UTHM students. The objectives include assessing the level of attitudes and civic skills of students before and after participating in the program and analyzing the differences that exist. A quantitative survey design was employed, utilizing pre- and post-tests to measure changes in attitudes and civic skills. The study involved students from the Faculty of Technical and Vocational Education taking the subject of Sociology of Education, using the Civic Attitude and Skills Questionnaire (CASQ) as a measurement tool. Limitations of the study include respondent honesty and environmental factors. The findings indicate a significant increase in students’ attitudes and civic skills following the SULAM program. This study demonstrates that service learning (SULAM) effectively enhances students’ attitudes and civic skills, contributing to the holistic development of students and providing empirical evidence to support the integration of theoretical learning with practical applications in higher education.